KESALAHAN PENGGUNAAN KONJUNGSI PADA MAKALAH MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA STKIP PGRI SUMATERA BARAT - Ilda Ilda (Horizon, 2021)
The backgroundof this research is because are still many errors of using conjunctions in the papers of student of the Indonesia Language and Literature education study program STKIP PGRI West Sumatera. This study aims to describe the misuse of conjunctions found in the papers of students of the Indonesian Language and Literature education study program STKIP PGRI West Sumatera. This type of research is a qualitative study using descriptive methods. The data source of this research is a paper writing scientific papers and discourse analysis of studens of Indonesian Language and Literature education study programs STKIP PGRI West Sumatera. The data in this study are errors using conjunctions in student papers. The results of data analisysis showed that in the papers written by students there were still many errors in their use. Errors of use of conjunctions obtained as many as four errors of use of conjunctions namely Pertema. Misuse of conjunctions and those placed at the beginning of sentences and excessive use of conjunctions and expressions are found in sentences. Secondly, errors in the use of conjunctions and those used at the beginning of a sentence and are not used to connect two languages in a sentence. Third, the use of conjunction errors students put the conjunction at the beginning of a sentence and is not used to connect the power between sentences. Fourth, mistakes in the use of conjunctions while those used at the beginning of a sentence, whereas this conjunction is used precisily in the middle of asentence and used to combine contradictory sentences. The most common use of conjunction errors in student papers is the use of conjunctions whereas, because many students use conjunctions while not in place ther efore the use of conjunctions used by students is declared wrong.